KETEPATAN PENYAMPAIAN LAPORAN KEUANGAN PERUSAHAAN SUBSEKTOR TELEKOMUNIKASI - Perdana, Gilang; Fuad, Muhammad; Meutia, Tuti (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
This study examines the effect of profitability, capital structure, and company size on the timeliness of financial statements submission of telecommunications sub-sector companies listed on the IDX. Profitability is measured by Return on Assets (ROA), capital structure by Debt to Equity Ratio (DER), and company size by log total assets. The data used in this study are the financial reports of companies in the telecommunication sub-sector for the 2007-2021 period. Logistic regression analysis is used as an analysis method. The results found that the profitability and company size had a negative and insignificant effect on the timeliness of financial statements submission. Meanwhile, the capital structure has a positive and insignificant effect on the timeliness of financial statements submission. Simultaneously, profitability, capital structure, and company size do not affect the timeliness of financial statements submission.